PENGARUH EDUKASI BERBASIS SELF CARE TERHADAP TINGKAT KELELAHAN PASIEN CHRONIC KIDNEY DISEASE - Elfina Natalia (Poltekkes Kemenkes Kalimantan Timur, 2018)
Chronic Kidney Desease was a progressive and irreversible kidney function disorder, usually treated with hemodialysis, a frequent complaint in hemodialysis patients is fatigue. The aim of this study was to see the effect of Based Self Care Education On level fatigue in Patient With Chronic Kidney Desease during Hemodialysis. The research was a quantitative study with quasi-experimental with control group pre test-post test design was used in this studi. The study was conducted at RSUD A. Wahab Sjahranie during May to June 2017. The total samples of 111 patients hemodialysis selected by purposive sampling. The subjects was divided into the interventions group consist of 83 patient who were given based self care education and the control group 28 patients. The results of the research were obtained after 6 weeks intervention, the Non-Parametric Test showed that Asymp Sig (2 tailed) = .00 or p-value <.05 the difference fatigue level between the intervention group to the control group, Odd Ratio was showed that self care-based education intervention group has a tendency to experience fatigue change rate of 1.22 times greater than control group. The ordinal logistic analyse result was showed that p = .00 or p-value <.05 there was a significant effected of Based Self Care Education intervention given to changes in fatigue. Conclusions of Based Self Care Education research have an influenced on decreased fatigue. The study has been recommended on intervention could be applied as one of the education given to patients during hemodialysis therapy.